ChemInform Abstract: Tandem Reaction of Propargyl Alcohols and N‐Tosyl Hydroxylamine: Switchable Synthesis of 2, 5‐Dihydroisoxazoles and 4‐Halo‐2, 5‐dihydroisoxazoles. Issue 15 (25th March 2013) - Zhu, Yuanxun; Yin, Guangwei; Sun, Lang; Lu, Ping; Wang, Yanguang
Abstract Efficient reaction conditions are reported for the conversion of propargylic alcohols (I) and (V) to 2, 5‐dihydroisoxazoles (III) and the 4‐halo derivatives (IV) and (VI).